An investigation of metacognitive awareness of reading strategies among TESL students / Nur Nadzirah Noh - Noh, Nur Nadzirah (Faculty of Education, 2014)
Readers need to develop their metacognition or metacognitive awareness in order to understand when, why and how to use reading strategies in dealing with comprehension difficulties. This is because knowing the reading strategies only is not sufficient. This study aims to investigate the metacognitive awareness of reading strategies among TESL students in UiTM Shah Alam. This study also examines the use of metacognitive knowledge, metacognitive reading strategies and how metacognitive knowledge influences metacognitive reading strategies in reading processes. This study was conducted quantitatively, using questionnaire to collect the required data. There were 85 students responded to this study from semester 1 until semester 4. The results revealed that the students' metacognition is poor as they have poor application of the reading strategies even though they have the knowledge in metacognitive. Hence, the findings call for pedagogical implications in an ESL classroom.